Fatty Acid Composition of the Fruits of Four Varieties of Pistacia vera L: Fatty Acid Composition of the Fruits Pistacia vera L - Boualem, Sid Ahmed; Ghrab, Mohamed; Bouhadi, Djilali; Elouissi, Abdelkader (Iranian Journal of Pharmaceutical Sciences, 2021)
The oil content, fatty acid compositions of pistachio nut (Pistacia vera L.) samples corresponding to four different varieties (Achouri, Adjmi, Batouri and Mateur), all cultivated in Algeria were determined. The fatty acid profiles of the oil extracted by the Soxhlet apparatus from four main commercial pistachio varieties, were determined by gas chromatography: palmitic (C16:0), palmitoleic (C16:1), margaric (C17:0), margarolic (C17:1), stearic (C18:0), oleic (C18:1), linoleic (C18:2), and linolenic (C18:3), oleic acid has been found as the most common monounsaturated fatty acid. Linoleic acid has the highest percentage among polyunsaturated fatty acids. There have been significant differences among pistachio cultivars regarding unsaturated fatty acids. Based on the oleic to linoleic acid (O/L) ratio, a quality index was determined for these four varieties: Achouri (3.39)  Batouri (3.12)  Adjmi (2.89)  Mateur (2.88). Principal Component Analysis (PCA) showed the pistachio varieties division into three distinct groups: Adjmi and Mateur (rich in C18.2), Batouri (rich in C16.1, C18.3 and C18.1), Achouri (rich in C16.0, C18.1).